2020
DOI: 10.1021/acssuschemeng.0c01863
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Discharge and Charge Behaviors of Li-CO2 Batteries with Carbon Nanotube Electrodes

Abstract: Li−CO 2 batteries are regarded as promising electrochemical devices to simultaneously capture CO 2 and deliver electric energy. Although efforts are made to exploring reaction routes and developing effective catalysts, the discharge and charge behaviors at different current densities and the intrinsic mechanisms are not reported. Herein, a Li−CO 2 battery with a carbon nanotube electrode is investigated. It is found that with an increase of the current density, the discharge voltage plateau gradually decreases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 51 publications
1
25
0
Order By: Relevance
“…Xie et al reported that the formation of amorphous Li 2 CO 3 was detected on the IrO 2 /MnO 2 catalyst through the synergistic effect of bimetallic oxide owing to the weak Li 2 CO 3 peaks in the XRD results . Similarly, in our previous work, the trace of some amorphous Li 2 CO 3 in the overall discharge products was observed on the electrode made of pure CNT when operated in a Li–CO 2 battery . Thus, under the same discharge capacity with the same current density, the weaker peaks related to Li 2 CO 3 may result from the growth of amorphous Li 2 CO 3 driving from the Co 0.1 Ni 0.9 O x /CNT electrode.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…Xie et al reported that the formation of amorphous Li 2 CO 3 was detected on the IrO 2 /MnO 2 catalyst through the synergistic effect of bimetallic oxide owing to the weak Li 2 CO 3 peaks in the XRD results . Similarly, in our previous work, the trace of some amorphous Li 2 CO 3 in the overall discharge products was observed on the electrode made of pure CNT when operated in a Li–CO 2 battery . Thus, under the same discharge capacity with the same current density, the weaker peaks related to Li 2 CO 3 may result from the growth of amorphous Li 2 CO 3 driving from the Co 0.1 Ni 0.9 O x /CNT electrode.…”
Section: Resultssupporting
confidence: 65%
“…39 Similarly, in our previous work, the trace of some amorphous Li 2 CO 3 in the overall discharge products was observed on the electrode made of pure CNT when operated in a Li−CO 2 battery. 40 Thus, under the same discharge capacity with the same current density, the weaker peaks related to Li 2 CO 3 may result from the growth of amorphous Li 2 CO 3 driving from the Co 0.1 Ni 0.9 O x /CNT electrode. Furthermore, the formation of the large-size discharge product is a disadvantage for the thoroughness in the electrochemical decomposition during the charge reaction.…”
Section: Electrocatalytic Decompositionmentioning
confidence: 97%
“…Carbon-based materials with high conductivity and porosity, such as graphene and carbon nanotubes (CNTs), are used as cathodes in Li–CO 2 batteries. 6–8 The cycle performance of the cells is largely improved, but the problem of high overpotential remains. To cope with this problem, electrocatalysts are introduced to decompose the insulating discharge product, Li 2 CO 3 .…”
Section: Introductionmentioning
confidence: 99%
“…3,4 The battery operation is the direct absorption and release of the fuel CO 2 during discharge and charge, respectively, exploiting excellent application prospects in the field of submarines mission and even Mars exploration at a high CO 2 atmosphere (∼96%). 5,6 To this end, multitudes of scientific efforts have been made to overcome technical barriers and promoting electrochemical performance, from the aspects of understanding the reaction mechanisms, 7,8 designing the available catalysts, 9,10 stabilizing the electrolyte compositions, 11,12 protecting the mental anodes, 13,14 modifying the operation conditions, 15,16 and improving the electrode structures. 17,18 Among various metal-CO 2 batteries, aprotic Li-CO 2 batteries have attracted broader attention because of the high equilibrium potential of 2.8 V and theoretical energy density of 1876 Wh kg −1 .…”
Section: Introductionmentioning
confidence: 99%
“…25 Further, a composite anode made of a carbon film deposited on metal Li was adopted to inhibit dendrites generation and keep electrochemical stability of 115 cycles with a cutoff capacity of 500 mAh g −1 , which presented three times better durability than the battery with the pristine Li metal. 14 In addition to battery materials, the operating conditions were also explored, such as the current density, 15 CO 2 partial pressure, 7 and working temperature. For example, at an ultralow temperature of −60 °C, a Li-CO 2 battery unexpectedly obtained a superior full discharge capacity to 8976 mAh g −1 and cycling performance of over 150 cycles (1500 h) at 100 mA g −1 .…”
Section: Introductionmentioning
confidence: 99%